The relationship between lecturers’ paralanguage and students’ satisfaction in Universiti Teknologi Mara, Kedah, Malaysia / Rosliza Md. Zani...[et. al.] - Md. Zani, Rosliza; Sabir Ahmad, Sarah; Isahak Merican, Farah Merican; Ahmad, Intan Nazrenee (Universiti Teknologi MARA Cawangan Pahang, 2011)
Satisfaction among students has become an essence particularly in an education industry. The industry is growing rapidly and competition is intense. Every organization is trying to become the most preferred education provider, especially in Malaysia and communication is the most important element to be stressed on to ensure students‟ sat-isfaction on services provided. Past researches indicated that, most meaning of conversational messages comes from non-verbal communication. Evaluation on students‟ perception on lecturers‟ paralanguage that would lead to their satisfaction to the services provided was examined. The results of the study illustrated that paralanguage which include vocal pitch, vocal loudness, pitch variation, pauses and fluency were shown to have an impact on students‟ satisfaction. Therefore, from this study, it can be inferred that students‟ in Malaysian universities are mostly observant on the vocal pitch of their lecturers when lectures are delivered to them. The present study caters for a wide variety of students and development professionals, especially those who are interested in non-verbal communication specifically paralanguage-related issues. It is highly hoped that the information gleaned from the present study may assist all service employees specifically in understanding better, the importance of paralanguage and its effects on students‟ satisfaction.